Палеогеновые сферииды (Bivalvia, Pisidiidae) Юго-Восточного Казахстана - Толстикова, Н.В. (Вестник зоологии, 1973)
A description is given of four new species of the superfamily Pisidiidae from Upper Eocene of the Zaysan depression: Amesoda martinsoni sp. n., A. kustovica sp. n., Musculium praelacustris sp. n., Pisidium jugatum sp. n. They are found in association with the fossil turtle, fishes, mammals and spore-pollinic complexes. Spheriides may be regared as an indicator of palaeogeographic environment. They live in the stagnant freshwater reservoirs with weak current and slightly alkalescent waters:- lakes, swamps, mort-rivers.